Historical Contestants: African American Documentary Traditions in On the Shoulders of Giants. (December 2017) - Sheppard, Samantha N.
This case study of Deborah Morales's On the Shoulders of Giants: The Story of the Greatest Team You've Never Heard Of (2011) examines African American documentary's relationship to sports documentaries. On the Shoulders of Giants chronicles the experiences and cultural impact of the "Harlem Rens, " the first all-Black professional basketball team. Grounding the documentary in African American documentary film and video traditions, I explore how specific authorial, aesthetic, and representational practices and politics shape and structure the film's historical interventions. Just as the documentary centers the Rens's embodied (athletic and social) experiences, my study of these practices and politics privileges the real, represented, and referenced Black body/bodies in the film as a critical site of analysis for such interventions. In doing so, I read the Black sporting body as an expressive, communicative body with "critical muscle memory, " an embodied history represented on screen that goes beyond the film's diegesis, that engages social issues, conditions, and changes specific to Black lived and imagined experiences. In turn, I suggest that Black sports documentaries are discourses that document, are indicative of, and construct critical muscle memory.